CLASSROOM INTERACTION: TEACHER AND STUDENTS PERCEPTION ON DIALOGUE IN PRIMARY SCIENCE CLASSROOM - Ramli, Munasprianto; Yohana, Media Putri (EDUSAINS, 2018)
INTERAKSI DALAM RUANG KELAS : PERSEPSI GURU DAN SISWA MENGENAI DIALOG DALAM PEMBELAJARAN SAINS DI SEKOLAH DASAROOM AbstractThis study aims to explore the teachers and students‟ perspective on classroom dialogue and its purpose in primary science classrooms that implement the new integrated curriculum in Indonesia. Research on the process of teaching and learning through classroom talks has been carried out over the last forty or so years. In the field of science education, classroom talks have become a central issue in developed countries within last twenty years. Although research focused in this topic is growing rapidly in Western countries, this is not the case in Indonesia. Few studies have dealt with classroom talk in Indonesia. We gathered our data during a period of four months by video recording, targeting lessons of classroom discussions in two primary schools in the Greater Jakarta area in Indonesia. To support data generated from classroom observation, I interviewed teachers and a sample of students in each class. Data were analysed using sociocultural discourse analysis. This study suggests that providing a room for students to interact and share with each other has changed the approach of learning science in the classroom. Classroom talk both in small groups and involving the whole class altered to pedagogical dynamics from a teacher centered approach to student centered one. The study also reveals that classroom talks did not only encourage students to develop their zone proximal development but also help them to learn the values of democracy.AbstrakPenelitian ini bertujuan untuk mengeksplorasi persepsi dari guru dan siswa sekolah dasar terkait dengan interaksi dan dialog yang terjadi dalam pembelajaran sains di kelas mereka. Penelitian terkait interaksi dan dialog dalam proses belajar mengajar sudah berlangsung selama empat puluh tahun lebih. Dalam  bidang pendidikan sains, topik ini baru menjadi salah satu isu sentral penelitian dalam dua puluh tahun terakhir, khususnya di negara maju. Sayangnya di Indonesia, kajian ini belum banyak di teliti. Literatur dan kajian terkait dialog dalam pembelajaran sains baik di sekolah dasar maupun sekolah menengah masih sangat terbatas sekali. Data dalam penelitian ini dikumupulkan dalam kurun waktu empat bulan di salah satu sekolah di wilayah selatan Jabodetabek.. Peneliti melakukan interview dengan guru dan siswa berdasarkan gambar dan video pembelajaran kelas mereka. Data kemudian dianalisa dengan menggunakan diskursus analisis sosio kultural. Dari hasil penelitian terlihat bahwa memberikan kesempatan untuk berinteraksi didalam kelas telah mengubah pendekatan dan dinamika dalam pembelajaran sains. Penelitian ini juga menunjukan bagaiaman interaksi dan dialog dalam pembelajajaran sains tidak hanya membantu mengembangkan kemampuan siswa dalam wilayah zone proximal development mereka, akan tetapi juga mendukung siswa dalam belajar nilai kehidupan termasuk nilai-nilai demokrasi.